DESIGN AND DEVELOPMENT OF EMPLOYEE PERFORMANCE ASSESSMENT APPLICATION BASED ON WEBSITE USING PAIRED COMPARISON METHOD AT UD TBRK ROASTERY - Irsyadi, Muhamad Haidir; Supriyanto, Antok; Sunarto, Dewiyani (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2021)
UD. TBRK Roastery a private company engaged in the manufacture and sale of local and imported coffee beans. The company was founded in 2016 and the founder of the company is Bowo Sundoro. The center of the company is located at Jalan Manukan Dalam Blok 14 J No. 12 Surabaya. One of the processes is a performance appraisal due to the employee development monitoring mechanism for each period (2 weeks). In conducting the assessment process, problems often occur such as the loss of the performance appraisal file in the previous period or during the ongoing period, the absence of a specific value range at the time of the performance appraisal, the calculation of the assessment which is often wrong, such as a mismatch with the content of the performance appraisal.Based on the problems described above, the solution needed is the creation of a website-based performance appraisal application using a paired comparison method that uses several criteria, including: efficiency, concern, enthusiasm, greeting, ethics, estimation, honesty, completeness, cooperation and passion. Application development uses the system development life cycle (SDLC), which consists of four stages, namely communication, planning, construction, and deployment. The results obtained from this study are in the form of a website-based performance appraisal application using the paired comparison method. This application can perform an appraiser selection process, performance appraisal using paired comparison, namely by performing automatic calculations when the owner or supervisor enters the value into the system. This application generates a performance appraisal report.